Assessing the impact of geographical indication socio-environmental practices on consumer behavior: the mediating role of pride and shame in word-of-mouth and purchase intention for coffee - Artêncio, Mateus Manfrin (2024)
This study investigates the influence of geographical indication (GI) socio-environmental practices on consumer word-of-mouth (WOM) and purchase intention (PI) regarding coffee, with a focus on the mediating roles of pride and shame. The research aims to assess how positive and negative socio-environmental practices associated with GIs affect consumer responses and explores potential moderating effects of individual psychological traits, such as the need to belong, empathy, public self-consciousness, and product involvement. Additionally, the study evaluates how consumer concern for the environment, fair labor practices, and the importance of GI information moderate these relationships. The study employed an experimental design using scenario-based manipulations, where participants were exposed to both favorable and unfavorable socio-environmental practices of GIs. Data were collected from a sample of 1,200 Brazilian coffee consumers, and the results were analyzed using mediation and moderation models. The findings confirm that favorable GI practices evoke feelings of pride, which influence both WOM and PI, while unfavorable practices trigger shame, leading to negative WOM and reduced PI. However, most moderating variables (need to belong, public selfconsciousness, and product involvement) did not significantly affect the relationship between GI practices and the mediators. Empathy emerged as a significant moderator, amplifying the effects of both pride and shame on dependent variable. Contrary to expectations, concern for the environment, fair labor, and the importance of GI information did not significantly moderate the effects of pride and shame on WOM or PI. These findings suggest that emotional responses to GI practices are primarily driven by perceptions of the practices themselves, rather than by broader socio-environmental concerns. Besides, results challenge assumptions about the universal impact of ethical concerns and offer a refined understanding of the emotional mechanisms driving consumer behavior in GI contexts. The study provides practical implications for coffee producers and marketers, emphasizing the importance of highlighting positive socio-environmental practices to foster consumer pride and drive positive WOM and PI. Tailoring marketing strategies to appeal to empathetic consumers may further enhance the impact of socio-environmental messaging, leading to stronger consumer engagement and advocacy for GI products.